Research on the epitaxial direction control and mechanism of polycrystalline diamond grains - Li Junpeng; Ren Zeyang; Zhang Jinfeng; Zhang Jincheng; Su Kai; Meng Jintao; Zhu Liaoliang; Li Yijiang; Chen Junfei; Wang Hanxue; Hao Yue (Functional Diamond, 2024)
The control of diamond film growth is crucial for the application of diamond films. In this article, different diamond film samples were prepared by adding nitrogen and oxygen in different proportions during the growth process. The key conditions for controlling the growth of diamond film with preferred orientation were obtained using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy characterizations. During the growth process, the growth of the diamond film with (100) preferred orientation could be achieved by adjusting nitrogen content. It was necessary to introduce nitrogen and oxygen in the growth process, and precisely regulate the ratio of the two to obtain the (111) preferred orientation of the diamond film. When only oxygen was introduced during growth, the preferred orientation of the diamond could not be achieved, leading to a smaller grain size and poorer crystal quality. From the perspective of grain morphology to film morphology evolution, this study obtained the crystal orientation control conditions during the diamond film growth, which has important guiding significance for the application of the diamond film. This study seeks to drive progress in the large-scale growth of readily machinable diamond and the evolution of diamond-grain optical fiber sensing through comprehensive investigations into the correlation between the preferred orientation in polycrystalline diamonds and reaction conditions.